A translational approach to characterization and measurement of health-promoting school ethos. (9th August 2017) - Penney, Tarra L; McIsaac, Jessie-Lee D; Storey, Kate; Kontak, Julia C H; Ata, Nicole; Kuhle, Stefan; Kirk, Sara F L
Summary: A health promoting schools (HPS) approach is hypothesized to influence student health and wellbeing by promoting a 'school ethos' that reflects the physical environment, social relations, organisational structure, policies and practices within schools. This complex set of factors makes health promoting school ethos (HPSE) challenging to define and measure. This work sought to theorise, develop and pilot a measure of HPSE as the context for implementation of HPS initiatives. We used a multi-method, iterative process to identify relevant HPSE concepts through triangulation of conceptual literature, existing tools and the tacit knowledge of school stakeholders. The HPSE measurement tool was administered to 18 elementary schools through a principal and teacher survey and an environmental assessment, followed by the development of HPSE scores for each school. Testing for internal consistency of items was used to examine theorized concepts, and scores for each school are summarised. HPSE included eight conceptual dimensions with internal consistency ranging from α = 0.60 to α = 0.87. Total HPSE scores across schools ( N = 18) ranged from 1 to 8 (mean = 3.94, SD = 2.1), with 28–65% of schools reporting 'high' on respective HPSE dimensions. Schools included a heterogeneous mixture of HPSE scores, particularly across different dimensions. Our novel approach to tool development allowed us to conceptualize HPSE using a flexible process comprising different types and sources of evidence. The HPSE tool holds potential for identification and measurement of critical components of different school context as it relates to HPS.